Phase Measurement of Guided-Mode Resonance Device Using Digital Micromirror Device Gratings - Min-Xu Chiang; Jaturon Tongpakpanang; Wen-Kai Kuo (Photonics, 2021)
This paper reports on the measurement system of the phase difference between s- and p-polarization components of the light passing through a guided-mode resonance (GMR) device using a digital micromirror device (DMD) gratings as a digital phase-shifting device. The phase of the non-zeroth order diffraction beams of the grating pattern displayed on the DMD can exhibit a phase change when the grating pattern is shifted. Two nearest different diffraction orders of p-polarized and s-polarized beams can be used as the reference and measurement beams, respectively, and are combined to implement the phase-shifting interferometry (PSI). The phase difference between the s- and the p-polarization components of the incident light passing through the GMR device can be obtained by applying the four-step phase-shift algorithm to the DMD-based PSI system. Experimental results show that this measurement system has a phase detection limit of 1° and was able to obtain the abrupt phase difference curve of the GMR device versus the incident angle.